Mitochondrial trafficking and redox/phosphorylation signaling supporting cell migration phenotypes - Shannon, Nathaniel; Gravelle, Randi; Cunniff, Brian (Frontiers in Molecular Biosciences, 2022)
Regulation of cell signaling cascades is critical in making sure the response is activated spatially and for a desired duration. The precise control over cell signaling cascades through protein phosphorylation requires the local activation or inactivation of specific kinases and/or phosphatases to elicit a complete and thorough response. For example, A-kinase-anchoring proteins (AKAPs) contribute to the local regulated activity protein kinase A (PKA). The activity of kinases and phosphatases can also be regulated through redox-dependent cysteine modifications that mediate the activity of these proteins. A primary example of this is the activation of the epidermal growth factor receptor (EGFR) and the inactivation of the phosphatase and tensin homologue (PTEN) phosphatase by ROS. Therefore, the local redox environment must play a critical role in the timing and magnitude of these events. Mitochondria are a primary source of reactive oxygen species (ROS) and energy (ATP) that contributes to redox-dependent signaling and ATP-dependent phosphorylation events. The strategic positioning of mitochondria within cells contributes to intracellular gradients of ROS and ATP, which have been shown to correlate with changes to protein redox and phosphorylation status driving downstream cellular processes. In this review, we will discuss the relationship between subcellular mitochondrial positioning and intracellular ROS and ATP gradients that support dynamic oxidation and phosphorylation signaling and resulting cellular effects, specially associated with cell migration signaling.